Emotional, behavioral and social difficulties among children with type 1 diabetes mellitus - S Ahmed, Eman; M. M. Monazea, Eman; E Abdel- El Naser, Amera; A M Kotb, Safaa (International Journal of Advanced Nursing Studies, 2016)
Background: Children and adolescents with diabetes are at a greater risk for emotional and behavioral problems.Aim of the study was to assess behavioral, emotional and social difficulties of diabetic children and examine the association of these difficulties with demographic and disease related variables.Subjects and method: A cross sectional study of 423 diabetic children attended Sidy Galal health insurance outpatient clinic in Assuit city – Egypt was conducted. A similar number of healthy children matched for age, sex and socioeconomic status were included in the study as a control group used for comparison. Strength and Difficulty Questionnaire (SDQ) was used as a screening tool. The SDQ is a screening instrument consisting of five separate 5-item subscales for emotional symptoms, conduct problems, hyperactivity-inattention, peer problems, and prosocial behavior.Results: Most of diabetic children (92.9%) were in the abnormal group of the total score compared to 20.6% of the controls. In all SDQ subscales except prosocial, diabetic children had significantly higher percentages of abnormal indices than in controls (p value <0.001). Emotional, hyperactivity and conduct problems were significantly associated with age and sex of the child. Prolonged duration of illness was significantly associated with peer relationship problems. Glycemic control was not a significant risk factor for any problem.Conclusion: Many of diabetic children had behavioral and psychosocial problems. Age and sex of the child and duration of the disease were important determinants for these problems.Recommendation: Diabetic children need to be screened by psychologist and social worker to identify and manage any behavioral or emotional problems.